Efficacy and safety of treatment with anti‐tumor necrosis factor‐α drugs for severe impetigo herpetiformis. Issue 2 (9th October 2020) - Fukushima, Hidehiko; Iwata, Yohei; Arima, Masaru; Tanaka, Yoshihito; Sugiura, Kazumitsu
Abstract: Impetigo herpetiformis (IH) is a rare pustular dermatosis. It can be life‐threatening for both the mother and fetus and often causes therapeutic problems. However, there is no specific guideline for the treatment of IH and the evidence regarding the efficacy of treatments for IH has not been established. Herein, we report two cases of IH, which were successfully treated with anti‐tumor necrosis factor (TNF)‐α drugs. The serum levels of the drugs in the infants and mothers were examined using enzyme‐linked immunosorbent assay (ELISA). Case 1 was a 35‐year‐old, gravida 2, para 1, female patient in week 20 of pregnancy; she was treated with adalimumab (ADA) until delivery. Case 2 was a 26‐year‐old, gravida 1, para 0, female patient in week 30 of pregnancy; she was treated with certolizumab pegol (CZP) until delivery. In both cases, the skin lesions started regressing considerably after administration of the biologic agents. We examined the serum levels of the biologic agents in the mothers and infants using ELISA. In case 1, the ADA serum level in the infant was as high as that in the mother at birth; it then decreased below the lower limit of quantification at week 12 post‐delivery. In case 2, the CZP serum level in the infant was below the lower limit of quantification at birth. In this report, we revealed that biologic agents could be an effective treatment for severe IH and that CZP treatment can be considered safe for the mothers and fetuses.